Chronic Intermittent Hypoxia-Induced Dysmetabolism Is Associated with Hepatic Oxidative Stress, Mitochondrial Dysfunction and Inflammation - Fernandes, Joana L. (2023)
CCVC8485 from Junta de Castilla y Leon, Spain. F.O.M., J.F.S. and M.G.A. are supported with CEEC contracts from the Portuguese Foundation for Science and Technology (CEECIND/04266/2017, CEEC IND/02428/2018 and 2021.03439.CEECIND, respectively). This work was also supported by Fundação para a Ciência e a Tecnologia”—FCT IBIMED (UIDP/04501/2020 and UIDB/04501/2020), UMIB (UIDB/00215/2020, and UIDP/00215/2020), ITR—Laboratory for Integrative and Translational Research in Population Health (LA/P/0064/2020), for the PhD student Patrícia C. Braga (UI/BD/150750/2020). Publisher Copyright: © 2023 by the authors.